2a+a+6-13=

Simple and best practice solution for 2a+a+6-13= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+a+6-13= equation:


Simplifying
2a + a + 6 + -13 = 0

Reorder the terms:
6 + -13 + 2a + a = 0

Combine like terms: 6 + -13 = -7
-7 + 2a + a = 0

Combine like terms: 2a + a = 3a
-7 + 3a = 0

Solving
-7 + 3a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3a = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 3a = 0 + 7
3a = 0 + 7

Combine like terms: 0 + 7 = 7
3a = 7

Divide each side by '3'.
a = 2.333333333

Simplifying
a = 2.333333333

See similar equations:

| 2a+a+6-13 | | -3y-15=7y+25 | | x+8forx=5 | | 3-2(n-9)=9 | | 2y+6x=8 | | -4=n-2+3 | | 34+x=64 | | 9/8-(-1/2-5/2) | | 2/7=6x/4x+17 | | 22+7c=-4c | | a/29=5p | | -1=8+2x+1 | | 4(2x+1)^2+5(2x+1)=4 | | x/4+3=(x-3)/3 | | -3m+m=-6 | | 3/v=m/22 | | 9n=9+12n | | x+x+10+220-3x=180 | | 9-15x-5-6x=7 | | -7y+4=5y-2y-3 | | 11v+5v--5=-11 | | 119-6x=39x+24 | | 2-x=-(30/(x-1)) | | (7/4)+1/5(x)-(3/2)=(4/5)x | | 3u=19.2 | | 16+8x=25+15x+3 | | 2-x=-30/(x-1) | | 48-3x=0 | | -12=-7k-5k | | 2-x=30/(x-1) | | 15t^2-22tv-5v^2=0 | | 2x/5+8=13/5 |

Equations solver categories